"So, Don't You Want Us Here No More?" Slow Violence, Frustrated Hope, and Racialized Struggle on London's Council Estates. Issue 3 (27th May 2022) - Lees, Loretta; Hubbard, Phil
ABSTRACT: Since 1997, over 50, 000 homes have been demolished to allow for the "renewal" of council estates in London. This has involved the "decanting" of short and long-term tenants, as well as those leaseholders who bought their homes under "right to buy" legislation. Often described as "social cleansing", the racialized dimensions of these displacements remain under-explored despite asizable literature documenting the connections between race, place and state-subsidized housing in Britain. Drawing on interviews with Black, Asian, and Minority Ethnic estate residents– including many active in housing movements– this paper shows that this displacement is understood in relation to histories of racial discrimination, the destruction of ethno-cultural infrastructures, and long-standing racialized inequalities. These themes resonate with apolitics of resistance grounded in aracialized class consciousness that seeks to intervene more broadly in the politics of capital and the state.